2021
DOI: 10.1021/acs.langmuir.1c00511
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Glyphosate by a Water-Gated Organic Field-Effect Transistor with a Microfluidic Chamber

Abstract: This paper reports the development of a real-time monitoring system utilizing the combination of a water-gated organic field-effect transistor (WG-OFET) and a microfluidic chamber for the detection of the herbicide glyphosate (GlyP). For the realization of the real-time sensing with the WG-OFET, the surface of a polymer semiconductor was utilized as a sensing unit. The aqueous solution including the target analyte, which is employed as a gate dielectric of the WG-OFET, flows into a designed microfluidic chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…[18] However, while these works try to model and assess the causes of the EGOT instabilities, they lack a systematic study of the effects of the application of an EBS, which is a fundamental aspect to be taken into account in specific applications such as real-time biosensing, where the measurement protocol may introduce an additional and unwanted signal variation. [19,20] In this work is therefore reported a study on the stability of EGOTs based on two commercial p-type semiconductive polymers, with particular focus on the impact of the EBS on the device performances. For this study, two polymers are compared, namely P3HT and poly [3-(5-carboxypentyl)thiophene-2,5-diyl] (P3CPT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] However, while these works try to model and assess the causes of the EGOT instabilities, they lack a systematic study of the effects of the application of an EBS, which is a fundamental aspect to be taken into account in specific applications such as real-time biosensing, where the measurement protocol may introduce an additional and unwanted signal variation. [19,20] In this work is therefore reported a study on the stability of EGOTs based on two commercial p-type semiconductive polymers, with particular focus on the impact of the EBS on the device performances. For this study, two polymers are compared, namely P3HT and poly [3-(5-carboxypentyl)thiophene-2,5-diyl] (P3CPT).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] However, while these works try to model and assess the causes of the EGOT instabilities, they lack a systematic study of the effects of the application of an EBS, which is a fundamental aspect to be taken into account in specific applications such as real‐time biosensing, where the measurement protocol may introduce an additional and unwanted signal variation. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been proposed in the literature for the integration of such devices in microfluidic platforms. Asano et al demonstrated the real time detection of glyphosate in water exploiting a microfluidics integrated EGOT [7], while White et al developed a versatile floating gate transistor for the label-free detection of DNA [8] and proteins [9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,15 ] While some of these studies demonstrated real‐time sensing, including the quantification of changes in solute concentration over time and the transport rate of molecules at the solid–liquid interface during crystallization, none have explored the continuous monitoring of biomolecule recognition (i.e., binding of carbohydrates, lipids, nucleic acids, and proteins). [ 16,17,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6,15] While some of these studies demonstrated real-time sensing, including the quantification of changes in solute concentration over time and the transport rate of molecules at the solid-liquid interface during crystallization, none have explored the continuous monitoring of biomolecule recognition (i.e., binding of carbohydrates, lipids, nucleic acids, and proteins). [16,17,11] In this work, a sensing platform based on an array of EGOFETs integrated with a microfluidic cell is demonstrated for real-time detection of the hybridization of DNA under a flowing electrolyte with <1 s temporal resolution. The array configuration was adopted because sensor platforms typically require parallel sensing to rapidly quantify multiple analytes in a single, precious biological sample, and to increase detection reliability for an individual analyte by using multiple replicates of individual devices on a single substrate.…”
Section: Introductionmentioning
confidence: 99%